2017
DOI: 10.1371/journal.pcbi.1005299
|View full text |Cite
|
Sign up to set email alerts
|

Computational Analysis of Residue Interaction Networks and Coevolutionary Relationships in the Hsp70 Chaperones: A Community-Hopping Model of Allosteric Regulation and Communication

Abstract: Allosteric interactions in the Hsp70 proteins are linked with their regulatory mechanisms and cellular functions. Despite significant progress in structural and functional characterization of the Hsp70 proteins fundamental questions concerning modularity of the allosteric interaction networks and hierarchy of signaling pathways in the Hsp70 chaperones remained largely unexplored and poorly understood. In this work, we proposed an integrated computational strategy that combined atomistic and coarse-grained simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
157
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(166 citation statements)
references
References 150 publications
(174 reference statements)
5
157
0
1
Order By: Relevance
“…Our work also points to the importance of these residues, but we find the dynamics of the linker to be better characterized as ordered segments with connecting hinges at Lys 387 and Leu 391 . Stetz and Verkhivker (13,14) also posit that several linker residues interact with the SBD, which is consistent with the observations made here. Similarly, Penkler et al (15) observed linker interactions with the SBD consistent with our observations.…”
Section: Hsp70 Interdomain Linker Enables Allosterysupporting
confidence: 90%
See 2 more Smart Citations
“…Our work also points to the importance of these residues, but we find the dynamics of the linker to be better characterized as ordered segments with connecting hinges at Lys 387 and Leu 391 . Stetz and Verkhivker (13,14) also posit that several linker residues interact with the SBD, which is consistent with the observations made here. Similarly, Penkler et al (15) observed linker interactions with the SBD consistent with our observations.…”
Section: Hsp70 Interdomain Linker Enables Allosterysupporting
confidence: 90%
“…We note, however, that both the ADP-bound and substrate-, ADPbound forms of DnaK simulated by Chiappori et al (11,12) were significantly more collapsed than would be consistent with experiments. Stetz and Verkhivker (13,14) propose that several linker residues are important in allostery based on a combination of evolutionary co-variance and dynamic character. Among these are Gly 384 , Asp 385 , Val 386 , Lys 387 , Leu 390 , Asp 393 , and Thr 395 , which they propose to be hinge residues, in either forward or reverse allosteric pathways.…”
Section: Hsp70 Interdomain Linker Enables Allosterymentioning
confidence: 99%
See 1 more Smart Citation
“…Though no model for the mechanistic role of the D HPD -R NBD interaction per se has been previously put forth, the functional connection between these residues is well supported by genetic and biochemical data. Alteration of either R NBD or residues interacting with it (D SBD and D Lk ) 10, 11,14,17,34,38 disrupt allosteric communication between domains, resulting in a somewhat increased basal activity and ineffective stimulation by its JDP partner, DnaJ in the case of DnaK 14 and Hsc20 in the case of Ssc1 ( Supplementary Fig. S4).…”
Section: Discussionmentioning
confidence: 99%
“…Текущая задача исследователей синтеза белка (трансляции) в этом контексте формулируется так: «our understanding of how basic ribosome processes, including mRNA decoding, peptide bond formation, mRNA, and tRNA translocation and cotranslational transport of the nascent peptide, are regulated» [24]. С этим трудно и нет смысла спорить, и слава тем специалистам, которые двигаются в этом направлении, применяя самые современные методы микроскопии, рентгеноструктурного анализа, направленного мутагенеза и самых изощренных компьютерных симуляций [25,26,27,28,29].…”
Section: синтез белка как объект физико-математического исследования 345unclassified